Inovação no setor de malharia retilínea : uma análise nas indústrias de Caxias do Sul - Ganzer, Paula Patricia (My University, 2014)
The practice of innovation contributes to economic development by creating the opportunity to develop new markets and improve the existing markets, generating benefits for producers and consumers of products and services news or improved by innovation. The textile sector encompasses a set of activities that provide the appearance of various segments of textile industries, since the origin of raw material, natural or artificial, to the finish of the final product. This dissertation aimed to investigate the innovations of the flat knitting sector occurred on the period 2008 to 2011, and through the literature review identify the changes in the industry since the 80’s, in Brazil, to the innovations of the industrial flat knitting of Caxias do Sul, by the four dimensions of innovation, according to the Oslo Manual (2005): product innovation, process innovation, marketing innovation and organizational innovation. The research method used has qualitative and quantitative approach, using the applied nature, exploratory and descriptive purposes. The technique proceeding used was the multiple case study, and the qualitative phase used exploratory and descriptive methods. In the quantitative phase, it was used a survey with a structured questionnaire as an instrument for data collection, which was applied to managers and/or owners of industries of rectilinear mesh of Caxias do Sul, associated to FITEMASUL of Caxias do Sul, with a total population of 23 companies. The data analysis took place in two stages, in the qualitative phase, we used the content analysis of the interview and the quantitative stage, it was used descriptive quantitative analysis, through the correlation of the data, in order to identify the level of relationship between variables of the theoretical construct. The results of the qualitative phase identified that the flat knitting sector of Caxias do Sul invests in innovation, according to the market demands and fashion trends. The quantitative results, aimed to verify relationships between variables of innovation and industry identified correlations between the variables of innovation. In moderate positive correlations (0,5 ≤ p < 0,8) it was identified a correlation between the variable: annual revenues, with the variables: number of employees and amount invested in marketing innovation, the variable: number of employees with variable: amount invested in marketing innovation, the variable: skilled labor with the variables: amount invested in product innovation and value invested in organizational innovation, the variable: amount invested in product innovation with the variable: value invested in marketing innovation, the variable: amount invested in product innovation with the variable: amount invested in organizational innovation. In the weak positive correlations (0,1 ≤ p < 0,5) it was identified correlation between the variable: number of employees with variables: amount invested in product innovation, value invested in organizational innovation and the variable: skilled labor. [resumo fornecido pelo autor]
A prática da inovação contribui para o desenvolvimento econômico por oportunizar a criação de novos mercados e o aperfeiçoamento de mercados existentes, gerando benefícios para produtores e consumidores de produtos e serviços novos ou melhorados pela inovação. O setor têxtil engloba um conjunto de atividades que proporcionam o surgimento de indústrias dos diversos segmentos têxteis, desde a origem da matéria-prima, natural ou artificial, até o acabamento do produto final. Esta dissertação de mestrado objetivou identificar as inovações do setor de malharia retilínea ocorridas no período de 2008 a 2011 e, a partir da análise da literatura, identificar as mudanças no setor, desde a década de 80, no Brasil, até as inovações do setor industrial de malharia retilínea do município de Caxias do Sul, por meio das quatro dimensões da inovação, segundo o Manual de Oslo (2005): a inovação de produto, de processo, de marketing e organizacional. O método de pesquisa utilizada possui abordagem qualitativa e quantitativa, de natureza aplicada, com objetivos exploratório e descritivo. O procedimento técnico utilizado foi o estudo de caso múltiplo, sendo a fase qualitativa, de cunho exploratório e descritivo. Na fase quantitativa, foi utilizada uma survey, com um questionário estruturado como instrumento de coleta de dados, que foi aplicado aos gestores e/ou proprietários das indústrias de malhas retilíneas de Caxias do Sul, associadas no FITEMASUL de Caxias do Sul, totalizando uma população de 23 empresas. A análise dos dados aconteceu em duas etapas, na etapa qualitativa, foi utilizada a análise de conteúdo da entrevista e na etapa quantitativa, foi utilizada a análise quantitativa descritiva, através da correlação dos dados obtidos, para a identificação do nível de relação entre as variáveis do construto teórico. Os resultados da fase qualitativa identificaram que o setor de malharia retilínea de Caxias do Sul, investe em inovação, de acordo com as exigências do mercado e as tendências de moda. Os resultados quantitativos, cujo objetivo foi verificar relações entre variáveis da inovação e da indústria, identificaram correlações entre as variáveis. Nas correlações moderadas positivas (0,5 ≤ p < 0,8) houve correlação entre a variável: faturamento anual, com as variáveis: número de colaboradores e valor investido em inovação de marketing; a variável: número de colaboradores com a variável: valor investido em inovação de marketing; a variável: mão de obra qualificada com as variáveis: valor investido em inovação de produto e valor investido em inovação organizacional; a variável: valor investido em inovação de produto com a variável: valor investido em inovação de marketing; a variável: valor investido em inovação de produto com a variável: valor investido em inovação organizacional. Nas correlações fracas positivas (0,1 ≤ p < 0,5) houve correlação entre a variável: número de colaboradores com as variáveis: valor investido em inovação de produto, valor investido em inovação organizacional e a variável: mão de obra qualificada. [resumo fornecido pelo autor]
Keywords: Indústria têxtil - Caxias do Sul (RS); Inovações tecnológicas; Malha - Indústria; Setor de Malharia Retilínea; Flat Knitting Sector